Exploring approaches to identify, incorporate and report patient preferences in clinical guidelines: Qualitative interviews with guideline developers. Issue 4 (April 2021) - Kim, Claire; Berta, Whitney B.; Gagliardi, Anna R.
Highlights: We interviewed 17 patients, 16 clinicians, and 17 managers from 7 countries. Organizations varied in approaches for identifying and incorporating preferences. Few organizations explicitly reported preferences or their impact on guidelines. Challenges included skepticism, limited guidance, and token patient participation. Findings included many facilitators of developing preference-informed guidelines. Abstract: Background: Clinical guidelines informed by patient preferences are more likely to be used and widely advocated, yet research shows that few guidelines reflect patient preferences. Objective: Explore how developers generate guidelines informed by patient preferences. Patient Involvement: Seventeen patients were involved as interview participants. Methods: Using a basic descriptive approach, we conducted and analyzed semi-structured telephone interviews with 50 participants who were involved in developing guidelines on various topics. The sample included 17 patients, 16 clinicians and 17 managers from a total of 7 countries. Results: Participants used one or more approaches to identify preferences, patient panelists, focus groups, surveys and review of published research, despite acknowledging they identified similar preferences. Participants said they incorporated preferences in all guideline development steps, but provided little detail of specific processes. Few participants said their guidelines explicitly reported how patients were engaged, preferences identified, or how preferences influenced development processes or the guideline. Enablers were patient and clinician training, supportive coordinators and chairs, involving experienced patients, and assistance from qualitative and review experts. Barriers were finding and preparing patients, clinician skepticism about benefits, and token patient involvement. Participants recommended research on how to generate preference-informed guidelines. Discussion: Ideal approaches to identify, incorporate and report patient preferences in guidelines are unclear and unproven. Practical Value: Findings revealed specific ways that developers can enhance their processes (e.g. patient training, supportive coordinators and chairs, involve experts in qualitative researcher and systematic reviews) and key issues that warrant ongoing research (e.g. how best to incorporate and report preferences).